A REVIEW ARTICLE ON THE MENTAL HEALTH ACT IN INDIA: A LEGAL AND SOCIETAL EVOLUTION - Purbita Das (The Bioscan, 2025)
Mental health legislation in India has undergone significant transformation, reflecting shifts in societal attitudes, international obligations, and the growing awareness of human rights. This article explores the evolution of mental health laws in India, focusing on the Mental Healthcare Act, 2017, which replaced the outdated Mental Health Act of 1987. The article analyzes key provisions, evaluates the Act’s impact, and highlights implementation challenges, offering suggestions for a more inclusive and effective mental health care framework. This article analyzes the historical and legal development of mental health legislation in India, critically examines the features and impact of the 2017 Act, and suggests strategies to bridge the gap between policy and practice. To truly transform mental health care in India, the Mental Healthcare Act must be supported by systemic reforms, increased public awareness, and sustained political will, making mental health a central component of India’s public health and social justice agenda.